Dosimetry of Bone-Seeking Radiopharmaceuticals for Palliative Therapy of Bone Metastases: A Simulation Study Using GATE Monte Carlo Code - Saman Dalvand; Hossein Rajabi; Ameneh Omidi; Etesam Malekzadeh (Frontiers in Biomedical Technologies, 2020)
Purpose: Radiopharmaceutical Therapy (RPT) is one of the effective methods for pain palliation of bone metastases. Bone marrow is a critical organ in bone structure whose absorbed dose should be kept below a certain threshold. The purpose of this study was to calculate and compare absorbed doses of bone-seeking radiopharmaceuticals used in the palliative treatment of bone metastases.